Clinical outcome of tetanus based on dakar tetanus severity score in paediatric intensive care unit of a tertiary care hospital - Jamil, Anila; Sarwar, Muhammad; Kausar, Fareeha; Sultan, Nighat; Aslam, Ambreen; Azeem, Umer Waqar (Journal of Rawalpindi Medical College, 2022)
Objective: To evaluate the validity of Dakar scoring system in predicting the outcome of tetanus in children of post neonatal age. Method: A prospective single center study conducted at ICU (Intensive Care Unit) of –removed for blind review-- 131 children with diagnosis of tetanus from January 2020 to June 2021 by analyzing demographic and clinical parameters. Results: Mean age of children was 8.11 ± 3.45 years with male predominance 91(69.5%). Major proportion of children were in range of 5-10 years comprising 65(50%). Period of onset of spasm was < 2 days in 92(70%) that correlate well with shorter incubation period (p-value <0.001). Mean duration of ICU stay was (18.81 ± 11.73) days. Only 14(10.7%) received three doses of vaccination but no one received booster dose. In majority of patients trauma due to road traffic accident 86(65.6%) was the predisposing factor followed by ear discharge 31(23.7%) and other causes 14(10.7%). Out of 131 patients 104(79.3%) received mechanical ventilation because of disease severity. Regarding outcome mild cases 2(1.5%), moderate 61(46.6%) and severe were 68(51.9%) according to Dakar scoring system and out of these severe cases 18(13.7%) expired (p-value < 0.001). However, 53(40.4%) discharged, 50(38.1%) shifted out to other wards after stabilization and 10(7.6%) left against medical advice. (p-value 0.001) Conclusion: Dakar scoring system correlates well with disease severity and should be adopted to aid clinical triage and management as with effective and appropriate treatment patients can have good prognosis. However, preventive aspects should be emphasized regarding booster dose of tetanus. Keywords: Tetanus, Outcome, Dakar scoring system